Preparation and characterization of benzoic acid-modified activated carbon for removal of gaseous mercury chloride. (15th November 2015) - Luo, JinJing; Lu, Jingjing; Niu, Qiang; Chen, Xiaobao; Wang, Zhongye; Zhang, Jieru
Abstract : Highlights: Activated carbon was modified with pre-heating treatment and benzoic acid impregnation. Gaseous HgCl2 adsorption experiments on activated carbon were conducted. Experiments showed that carboxylic and carbonyl groups promoted HgCl2 adsorption process. Carboxylic groups are believed to contribute the most to HgCl2 capture. Abstract: This article investigates the properties of surface oxygen-containing functional groups (SOFG) on activated carbons, and their effects on removal of gaseous mercury chloride (HgCl2 ). For this purpose, the surface of a coal-based commercial activated carbon BPL was modified by heating in an inert atmosphere and then impregnated with benzoic acid solution. Afterwards, all carbonaceous samples were tested for their HgCl2 adsorption capacities. Nitrogen (N2 ) adsorption, Fourier Transform Infrared Spectroscopy (FT-IR) and Boehm titration were applied to study the surface characteristics of carbon samples. It was found that after benzoic acid impregnation, the amounts of SOFG improved with the increasing of benzoic acid concentration, especially carboxylic and carbonyl groups. Adsorption experiments showed that higher HgCl2 adsorption capacities were obtained with more carboxyl and carbonyl groups. And the largest capacity obtained in this study was 484.7 μg/g of carbon with carboxyl and carbonyl concentrations of 0.570 mmol/g and 0.706 mmol/g, respectively. This suggests that carboxylic and carbonyl groups play predominant roles in HgCl2 removal. And carboxylic groups are believed to contribute more than that of carbonyl groups in HgCl2 capture process.